Methodology of management bodies during the planning of border operations to counter illegal activities at the state border - Voronyi, Serhii; Mysyk, Anatolii (Social Development and Security, 2024)
Purpose: to improve the quality of planning of border operations due to the improvement of the methodology of the management bodies of the State Border Service of Ukraine, which ensures the assessment of the predicted effectiveness and efficiency of the activities. Design/Method/Approach (only for empirical papers): the basis of the improved methodology of the management bodies of the SBGSU during the planning of border operations is the assessment of their effectiveness and efficiency. The methodology is based on a combination of planning techniques based on risk analysis and assessment of capabilities to counter threats. Findings: the methodology of the SBGSU management bodies during the planning of border operations has been improved and methodical recommendations have been provided for their planning in the areas of the state border where hostilities are not taking place. Theoretical implications (if applicable): the methodology of the study of the problems of state border protection received further development. A synergistic effect was obtained from the combination of the application of the planning methodology based on the capabilities to counter threats and the risk analysis methodology to solve management problems in the field of protection and protection of the state border. Originality/Value: the novelty of the proposed approach consists in establishing a connection between the level of threats of illegal activity and the capabilities of the State Security Service to perform the tasks of countering threats in accordance with the legally defined functions. The novelty of the improved methodology is the set of procedures for determining the need for their implementation, assessing effectiveness and efficiency, which provides justification for the creation of the capabilities of the State Border Service of Ukraine to perform tasks in the field of protection and protection of the state border by conducting border operations. Future research: justification of operational construction during the preparation and conduct of border operations at the state border. Study of issues of interaction in the system of integrated border management during border operations. Papertype: theoretical.